(untitled) - Bernal, J. D (Cambridge, Mass., 1954)
This first volume begins with the discussion of the particular nature and methodology of science. It then continues with a description of the emergence of science in the Stone Age, and traces its development through the full formulations of the Greeks to its development under Christendom and Islam in the Middle Ages.
Keywords: Civilization,Science and civilization,Văn minh,Văn minh và khoa học; History,Lịch sử